Improvement of adhesive toughness measurement - Meng, Qingshi; Zaman, Izzuddin; R. Hannam, Joshua; Kapota, Shepherd; Luong, Lee; Youssf, Osama; Ma, Jun (Elsevier Science Ltd, 2011)
The double cantilever beam (DCB) method for adhesive toughness measurement was improved by incorporating a sufﬁciently sharp crack made by a wedge-tapping method. A known route to producing cracks via loading–unloading cycles was proved unreliable because the cycles produced plastic deformation in the adhesive where new cracks propagated. Abnormally high toughness values with large standard deviations were obtained with cracks made by embedding a non-sticky insert. Only instantly propagated cracks made by tapping were sufﬁciently sharp to produce reproducible, accurate tough-ness measurements. However, toughened resin was insensiti